Influence of Mg(II) substitution on the structural, magnetic, and permeability properties of R-type hexagonal ferrites - Hassan, Zahoor Ul; Sadiq, Imran; Khan, Hasan Mehmood; Hussain, Sajjad; Sadiq, Farhan; Idrees, Mishal; Shahbaz, Muhammad; Saeed, Samreen; Imran, Muhammad; Riaz, Saira; et al. (European Journal of Chemistry, 2023)
A series of single-phase R-type hexagonal ferrites with the composition Sr1-xMgxFe4Sn2O11 (x = 0.0, 0.1, 0.2, 0.3) were manufactured using the auto-combustion sol-gel method sintered at 800 °C. The objective of this work was to study the effect of Mg additives on the structural, magnetic, and permeability properties of the synthesised material. The X-ray diffraction patterns revealed that all prepared samples have hexagonal structures. The scanning electron micrographs revealed the platelet-like structure of the grains, which would help enhance the magnetic permeability of the materials. Magnetic parameters were investigated in the range of applied field ±12.5 kOe. The hysteresis loops revealed the paramagnetic nature of all the synthesised samples. With the substitution of Mg contents, the maximum magnetization increased from 1.05 to 2.62 (emu/g) and the remanence from 0.02-0.09 (emu/g), while the coercivity also increased. The magnetic permeability was determined over the frequency range of 20 Hz to 20 MHz. The magnetic permeability of the synthesized hexagonal ferrites is enhanced due to the presence of grains having a platelet-like structure. Furthermore, the particle size calculated using Langevin equations varied in the range of 4.7 to 6.5 nm. The calculated magnetic permeability properties make this synthesised ferrite material useful for super-high-frequency devices.